2016
DOI: 10.1016/j.ypmed.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and instrumental support during childhood and biological dysregulation in midlife

Abstract: Objective To determine whether greater emotional and instrumental support during childhood is associated with less dysregulation across multiple physiological systems in midlife. Methods Data are from participants in the second wave of the Midlife in the United States study (2004–2005) who participated in a clinic-based assessment of health status. Emotional and instrumental support was measured using a seven-item scale (α=0.89) based on participant retrospective self-report. Biological dysregulation was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
4
21
0
Order By: Relevance
“…However, PCEs maintained an association with D/PMH independent from ARSES. Findings are both consistent with prior research showing that relational experiences in childhood are associated with adult social and relational skills and health 3,15,56,68 and also point to enduring effects of PCEs on D/PMH separate from their influence on adult ARSES. While PCEs associations with D/PMH were substantial and similar for adults reporting ACEs, associations were not statistically significant for those reporting no ACEs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, PCEs maintained an association with D/PMH independent from ARSES. Findings are both consistent with prior research showing that relational experiences in childhood are associated with adult social and relational skills and health 3,15,56,68 and also point to enduring effects of PCEs on D/PMH separate from their influence on adult ARSES. While PCEs associations with D/PMH were substantial and similar for adults reporting ACEs, associations were not statistically significant for those reporting no ACEs.…”
Section: Discussionsupporting
confidence: 89%
“…9,10 On the other hand, children with adverse childhood experiences (ACEs) are at risk for observable changes in brain anatomy, 11 gene expression, 12,13 and delays in social, emotional, physical, and cognitive development lasting into adulthood. [3][4][5][14][15][16][17] According to standardized measures, an estimated 61.5% of adults 18 and 48% of children 19 in the United States have been exposed to ACEs, with more than one-third of these having multiple exposures. 18,19 The wide-ranging negative associations between exposure to multiple ACEs and diminished adult and child health are well documented.…”
mentioning
confidence: 99%
“…Russek & Schwartz, 1997). Similarly, a recent study found that perceptions of being loved and cared for as a child is associated with reduced allostatic load among adults (Slopen, Chen, Priest, Albert, & Williams, 2016). And yet, to our knowledge, no studies have examined how lifetime social support or other protective psychosocial factors influence birth outcomes.…”
Section: Life Course Perspectivementioning
confidence: 86%
“…The Midlife in the United States study offers one example of how existing measures can be adapted. This study utilized a subset of the Childhood Trauma Questionnaire (Bernstein & Fink, 1998) to assess childhood support by asking seven questions about feeling loved and having an adult to provide care (Slopen et al, 2016). This measure does not capture strength of the support, variation in support over the life course, or the wide range of sources of support, but it does provide a foundation from which expanded measures can be created.…”
Section: Measurement Challenges and Recommendationsmentioning
confidence: 99%
“…Traditionally, research on the influence of childhood experiences on chronic disease risk has focused on how disadvantage during childhood (Doom et al, 2016; Lehman et al, 2005; Pollitt et al, 2007, 2008; Pollitt et al, 2005) confers elevated risk for poor outcomes, including cardiovascular diseases (Galobardes et al, 2006; Johnson et al, 2013; Loucks et al, 2011; Miller et al, 2011; Shonkoff et al, 2009). To date, limited research has considered the influences of positive experiences during childhood for cardiovascular wellbeing in later life (Appleton et al, 2013; Laitinen et al, 2013; Pulkki-Råback et al, 2015; Sood and Gidding, 2016; Lehman et al, 2005; Russek and Schwartz, 1997; Slopen et al, 2016; Sood and Gidding, 2016; Westerlund et al, 2013), in contrast to disease as the outcome (Lehman et al, 2005; Russek and Schwartz, 1997; Slopen et al, 2016; Westerlund et al, 2013). In this study, we examined the relationship between positive childhood experience and an ideal cardiovascular health in a large sample of adults in mid-life, and evaluated the extent to which education, depression, and social support in midlife mediate this association.…”
mentioning
confidence: 99%